Preparation and Photoluminescence Spectra of Organometallic Complexes Containing Nanoparticles as Random Gain Media - Atheer Abdulraheem Mahmood; Oday Atta Hammadi; Kais Rzaik Ibraheem (Universitas Gadjah Mada, 2022)
This work prepared organometallic complexes from the 8-hydroxyquinoline ligand linked to metal ions such as Ba2+, Ca2+, and Zn2+. The effects of metal ion type and adding nanoparticles to the complex solution on the absorption and photoluminescence characteristics of the prepared complexes were introduced. These nanoparticles were added to the prepared complex solutions to act as scattering centers to form random gain media with emission in the visible region of the electromagnetic spectrum. The random gain media made from the Znq2 complex with nanoparticles showed the best characteristics with good chemical and spectroscopic stabilities, high reliability, and reproducibility in addition to the low production cost and reasonably simple requirements.